NATIONAL COSTUMES AND THEIR SIGNIFICANCE - M.M. Qurbonova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: National dress is the beauty of every nation. National costumes are one of the factors that express the uniqueness, elegance and attractiveness of each nation. This article talks about the attention paid to the national dress in our country, the history of the origin of the national dress, the uniqueness of the national dress of each nation.